ManPy: an open‐source software tool for building discrete event simulation models of manufacturing systems. (30th August 2015) - Dagkakis, Georgios; Papagiannopoulos, Ioannis; Heavey, Cathal
Summary: In this paper, we present a new open‐source (OS) software library for building discrete event simulation objects with focus on manufacturing environments. ManPy stands for 'Manufacturing in Python' but employs a generic approach that can be extended to other types of business processes such as services, logistics and supply chain management. It is written in Python and makes use of the SimPy library to implement a process interaction world view. The goal in developing ManPy is to provide an expandable OS layer of well‐defined manufacturing objects, which can be used by users with multiple levels of expertise in discrete event simulation, namely, a super user and an industrial engineer. This object repository follows a structured architecture, allowing developers to extend it, exchange ideas and methodologies, with the goal of forming an OS community. We explain how ManPy is developed on SimPy, present its architecture and give examples of its utilization. We also give insight of how this work is planned to progress in order to attract software developers, modellers and practitioners in an OS community. Copyright © 2015 John Wiley & Sons, Ltd.